2016
DOI: 10.1016/j.fcr.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rice seed dressing with Paenibacillus yonginensis and silicon on crop development on South Korea’s reclaimed tidal land

Abstract: a b s t r a c tA field trial to investigate the effects of plant growth promoting bacteria (PGPB) Paenibacillus yonginensis (DCY84 T ) and/or SiO 2 seed coating on rice growth (Oryza sativa L.) was carried out on reclaimed tidal land in Taean County in South Korea. The field test was performed twice between May-October 2014 and May-October 2015, in a randomized complete block (RCB) design with three replications. Treatments consisted of: Mock, DCY84T -treated seeds, SiO 2 -coated seeds and DCY84 T -SiO 2 -trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
2
14
0
2
Order By: Relevance
“…Since the root is in tight contact with other microorganisms in the soil, the role of plant growth promoting bacteria (PGPB) as well as mycorrhiza, and their interaction with Si and abiotic stress factors should be also considered. This does not seem to be an intensively studied topic, however, some reports indicated that Si applied together with PGPB may help to overcome the drought stress or improve the vigor of plants grown in saline conditions [138,139].…”
Section: Effects Of Silicon In Plant Roots During Abiotic Stressesmentioning
confidence: 99%
“…Since the root is in tight contact with other microorganisms in the soil, the role of plant growth promoting bacteria (PGPB) as well as mycorrhiza, and their interaction with Si and abiotic stress factors should be also considered. This does not seem to be an intensively studied topic, however, some reports indicated that Si applied together with PGPB may help to overcome the drought stress or improve the vigor of plants grown in saline conditions [138,139].…”
Section: Effects Of Silicon In Plant Roots During Abiotic Stressesmentioning
confidence: 99%
“…Silica zeolite complex and two treatments with strain DCY84 T resulted in the highest head rice levels (86.8%) compared to a one-time treatment of DCY84 T (67.9%), and without strain DCY84 T treatment (46.4%). The PGPR treatment enhanced head rice levels by 40.4% [ 16 ]. Strain treatment also enhanced nitrogen uptake and increased levels of stored nitrogen in the rice grain, indicating that the strain DCY84 T enhanced plant nitrogen utilization with less nitrogen fertilizer application.…”
Section: Insights From the Genome Sequencementioning
confidence: 99%
“…Гістохімічні дослідження рису показали, що корені накопичують Si та розподіляють його рівномірно (Abe and Wakatsuki, 2011;Choi et al, 2016;Horgan et al, 2016), хоча вважалось, що він міститься переважно в епідермальних тканинах. У транспіраційних органах (листках) кремній концентрується в епідермальних тканинах, утворює подвійний кутикулярний кремнієвий шар, який захищає рослини від надмірної транспірації та грибкових патогенів.…”
Section: вступunclassified
“…Зміна біомаси гречки на дерново-літогенних ґрунтах на сіро-зелених глинах із додаванням кремнієвих добрив: 0,1%, 0,2%, 0,3% та 0,4% розчини SiO 2 У нашому вегетаційному експерименті біомаса рослин збільшувалась від 1,27 до 3,50 раза відносно контролю. У працях Choi et al (2016) обробка насіння рису SiO 2 збільшила удвічі свіжу біомасу, а сухув 1,7 раза відносно рослин, які попередньо не обробляли. Збільшився вміст білка в зерні з 6,0% до 7,2%.…”
Section: варіант експериментуunclassified